2015
DOI: 10.1080/15389588.2015.1092524
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of child victims in motor vehicle collisions in Panama

Abstract: In Panama, a lack of specific legislation on the use of child restraints (car seats) as well as a lack of information and awareness campaigns could be responsible for the high toll of child victims associated with motor vehicle collisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In a previous study, we demonstrated that the infant mortality rate in Panama from motor vehicle crashes is 3 to 4 times higher than the rates observed in a country with better child restraint legislation (Spain) [6]. That study concluded that the lack of specific legislation on the use of CRS (car seats), as well as the lack of information and awareness campaigns, could be responsible for the high number of child victims associated with motor vehicle collisions [6]. We have also documented our work and achievements in Panama through the generation of public policies on child road safety based on scientific evidence [26].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In a previous study, we demonstrated that the infant mortality rate in Panama from motor vehicle crashes is 3 to 4 times higher than the rates observed in a country with better child restraint legislation (Spain) [6]. That study concluded that the lack of specific legislation on the use of CRS (car seats), as well as the lack of information and awareness campaigns, could be responsible for the high number of child victims associated with motor vehicle collisions [6]. We have also documented our work and achievements in Panama through the generation of public policies on child road safety based on scientific evidence [26].…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, the economic cost of MVCs was just over 11 million USD (0.9% of Belize's GDP) [5]. A more recent study conducted in 2016 in Panama, a country with few traffic safety regulations for infants and children, showed that MVC-related infant and childhood mortality rate was four times higher than that of Spain, a country with stricter regulations on childhood retention systems (CRSs) [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motor vehicle accidents have an important place among childhood traumas and they are the leading cause of death in children aged 2-14 years in developed countries (11). Motor vehicle accidents consist of 30% of the trauma-related casualties aged between 0-19 (12).…”
Section: Discussionmentioning
confidence: 99%